Caries prevention with chlorhexidine-thymol varnish in high risk schoolchildren - Splieth C, Steffen H, Rosin M, Welk A (Blackwell Synergy, 2000)
In a prospective, randomised and blinded cohort study, the acceptance and effectiveness of a 3-monthly chlorhexidine-thymol varnish application was assessed in 8- to 10-yr-old children (n½29) with high caries incidence after brushing with a 1.23% fluoride gel. The children of the control group (n½25) brushed with a fluoride gel only. The standardised interview showed good acceptance of the varnish applications in spite of the bitter taste.